Global Production Sharing, Trade Patterns, and Determinants of Trade Flows in East Asia - Prema–Chandra Athukorala; Jayant Menon (Asian Development Bank (ADB), 2010)
Global production sharing—the breakup of a production process into vertically separated stages that are carried out in different countries—has become one of the defining characteristics of world trade over the past few decades. Any analysis of trade patterns or its determinants that ignores this phenomenon, and the trade in parts and components that it generates, is likely to result in erroneous conclusions. This study examines the extent and pattern of these flows, focusing on East Asia, and probes its implications for the analysis of the determinants of trade flows. World trade in parts and components increased from about 18.9% to 22.3% of total exports between 1992/93 and 2005/06. Most of this growth emanates from East Asia, with its share in total world exports increasing from 27% to 39% over the same period. There was a notable decline in Japan's share toward the end of this period, but this was more than offset by the rising importance of the People's Republic of China (PRC). In East Asia, most of this trade is in electronics. The econometric analysis reveals that parts and components are remarkably less sensitive to changes in relative prices; as a result, the sensitivity of aggregate trade flows to relative price changes diminishes as its share increases. This implies that exchange rate policy may be less effective in balance of payments adjustment, in countries where component trade is high and growing.
hdl:11540/1964
Keywords: F10; F13; F23; 330; Global production sharing; product fragmentation trade; determinants of trade flows; exchange rate policy